The genius - Kellerman, Jesse (G.P. Putnam's Sons, 2008)
When a retired cop recognizes the faces of murdered children in an art gallery exhibit, he and his assistant DA daughter Susan begin a search to find the artist of the portraits--and possibly crack open a forty-year murder case.